The Vibration Analysis by Margenau-Hill Transformation Method - Jaroslav Smutny; Daniela Sadlekova (Communications - Scientific letters of the University of Zilina, 2014)
The paper is devoted to the description and application of Margenau Hill transformation for vibration analysis. This is a transformation belonging to the large group of non-linear time-frequency transformations. The properties predestinated it to a successful use in the area of non-stationary and transitional signal analysis describing various natural processes. A very interesting application area of this transformation is its use for the vibration analysis of signals from railway traffic. The paper contains mathematical analysis of the transformation, case study and gained practical experience and recommendations for practice.